Examining the Effect of Kindlin-3 Binding Site Mutation on LFA-1-ICAM-1 Bonds by Force Measuring Optical Tweezers - McDonald, Craig; Morrison, Vicky L.; McGloin, David; Fagerholm, Susanna Carola (Frontiers in Immunology, 2022)
Integrins in effector T cells are crucial for cell adhesion and play a central role in cell-mediated immunity. Leukocyte adhesion deficiency (LAD) type III, a genetic condition that can cause death in early childhood, highlights the importance of integrin/kindlin interactions for immune system function. A TTT/AAA mutation in the cytoplasmic domain of the β2 integrin significantly reduces kindlin-3 binding to the β2 tail, abolishes leukocyte adhesion to intercellular adhesion molecule 1 (ICAM-1), and decreases T cell trafficking in vivo. However, how kindlin-3 affects integrin function in T cells remains incompletely understood. We present an examination of LFA-1/ICAM-1 bonds in both wild-type effector T cells and those with a kindlin-3 binding site mutation. Adhesion assays show that effector T cells carrying the kindlin-3 binding site mutation display significantly reduced adhesion to the integrin ligand ICAM-1. Using optical trapping, combined with back focal plane interferometry, we measured a bond rupture force of 17.85 ±0.63 pN at a force loading rate of 30.21 ± 4.35 pN/s, for single integrins expressed on wild-type cells. Interestingly, a significant drop in rupture force of bonds was found for TTT/AAA-mutant cells, with a measured rupture force of 10.08 ± 0.88pN at the same pulling rate. Therefore, kindlin-3 binding to the cytoplasmic tail of the β2-tail directly affects catch bond formation and bond strength of integrin–ligand bonds. As a consequence of this reduced binding, CD8+ T cell activation in vitro is also significantly reduced.